A novel anatomic classification to guide transcatheter aortic valve replacement for pure aortic regurgitation. Issue 12 (14th November 2022) - Chen, Yang; Lu, Zhi‐Nan; Yao, Jing; Wang, Mo‐yang; Niu, Guan‐Nan; Zhang, Hong‐Liang; Liu, Qing‐Rong; Zhao, Jie; Zhao, Zhen‐Yan; Perrin, Nils; Modine, Thomas; Wu, Yong‐Jian; et al.
Abstract: Background: The success of transcatheter aortic valve replacement (TAVR) in native aortic regurgitation (AR) is limited by the absence of calcified anchoring structures. We sought to evaluate transfemoral TAVR in patients with native AR using a novel aortic root imaging classification. Methods: From March to November 2021, 81 patients with severe AR were prospectively enrolled in 2 cardiac centers in China. All were evaluated using multidetector computed tomography (MDCT) and classified into 4 anatomic types in reference to transcatheter heart valve (THV) anchoring: Type 1: anchoring at the left ventricular outflow tract (LVOT), annulus, and ascending aorta (AA); Type 2: anchoring at the annulus and AA; Type 3: anchoring at the annulus and LVOT; and Type 4: anchoring at only 1 level or none at all. Based on the dual‐anchoring strategy, patients with Types 1–3 were considered TAVR candidates. Procedural and 30‐day outcomes were assessed according to Valve Academic Research Consortium‐3 definitions. Results: TAVR was performed in 32 (39.5%) patients (71.9 ± 8.0 years of age, 71.9% were male) using 2 self‐expanding THVs. Types 1, 2, and 3 comprised 13 (40.6%), 11 (34.4%), and 8 (25.0%) cases, respectively. The procedural and device success rates were 100% and 93.8%, respectively, with 2 THV migration. Eight patients (25.0%) required a permanent pacemaker, and 2 (6.3%) developed moderate paravalvular leaks. No deaths or other major complications occurred during the study. Conclusions: The novel anatomic classification and dual‐anchoring strategy were associated with a high procedural success rate with favorable short‐term safety and clinical outcomes.